Impact of graft-versus-host disease prophylaxis on immune reconstitution in patients after allogeneic hematopoietic stem cell transplantation - E. D. Mikhaltsova; N. N. Popova; M. Yu. Drokov; N. M. Kapranov; Yu. O. Davydova; V. A. Vasilieva; D. S. Dubnyak; U. V. Maslikova; I. V. Galtseva; L. A. Kuzmina; E. N. Parovichnikova; V. G. Savchenko (Медицинская иммунология, 2021)
The graft-versus-host disease (GVHD) is among the most common complications after hematopoietic stem cell transplantation (allo-HSCT). The main tools for GVHD prevention remain calcineurin inhibitors (cyclosporin A, tacrolimus), methotrexate, mycophenolate mofetil. Upon implementation of reduced-intensity conditioning regimens, antithymocyte globulin was widely introduced. However, negative effects upon reconstitution of T-cell immunity have been noted, thus increasing risk of severe infectious complications and disease relapse. With extended practice of HSCT from alternative (partially matched or haploidentical) donors, cyclophosphamide was increasingly used. Our aim was to study reconstitution of immune cell subpopulations in the patients undergoing bone marrow transplantation (BMT), when using different GVHD prophylaxis regimens, including the schedules with post-transplant CP usage. The study concerned 44 cases classified into 2 groups. The first one included patients with standard immunosuppressive therapy, antithymocyte therapy, cyclosporine A, methotrexate, mycophenolate mofetil. The second group included the patients who received CP as immunosuppressive drug combined with other treatments (cyclosporine A, methotrexate, mycophenolate mofetil). At specified control terms, (D+14, +30, +60, +90) the blood leukocyte subpopulations were assayed by means of multicolor flow cytometry. Absolute counts of CD4+ cells in HSCT recipients treated with CP post-BMT proved to be sufficiently lower at D+14 and +30, than in those treated with classical immunosuppressive therapy. However, at later terms, (D+60, +90), these differences were not observed. Moreover, in CP-treated bone marrow recipients, absolute numbers of CD8+ cells was significantly higher, compared to the patients who received conventional GVHD prophylaxis. Reconstitution of the studied lymphocyte populations in hematopoietic cell recipients did not depend on the GVHD prophylaxis regimen. Usage of CP combined with bone marrow as a source of stem cells, brings about sufficient decrease of some cell populations (CD4+; CD8+; NK cells) at early terms post-transplant. Administration of CP combined with hematopoietic stem cells as the source of hematopoietic graft seems to be more reasonable.